Occurrence of a beta-lactam-inducible penicillin-binding protein in methicillin-resistant staphylococci. - Ubukata, K (1985)
The mechanism of methicillin resistance was investigated in methicillin-resistant staphylococci (MRS) and in variants which had lost methicillin resistance. Phase-contrast microscopy showed that cells swelled at low concentrations of beta-lactam antibiotics in both MRS and variants which had lost methicillin resistance. Cells of variants which had lost methicillin resistance were lysed easily when higher concentrations of antibiotic were used. In contrast, MRS cells remained swollen at even higher concentrations of antibiotics. Furthermore, bacterial growth was inhibited at antibiotic concentrations much lower than MICs for MRS. Examination of the penicillin-binding proteins (PBPs) in MRS revealed that a new PBP-2' (molecular weight, 74,000) was induced in large quantity by exposure to beta-lactams. PBP-2' was produced constitutively in variants of MRS which had lost a penicillinase plasmid. The induction of PBP-2' by beta-lactams was not detected in variants which had lost methicillin resistance. High concentrations of beta-lactam were required for saturation of PBP-2'. The optimum antibiotic concentration for the induction of PBP-2' varied with the beta-lactam used as the inducer, and PBP-2' was produced in a larger amount at 32 degrees C than at 37 degrees C. From these results, we suggest that the mechanism of methicillin resistance depends on the induction of PBP-2', which may function as a detour enzyme for PBP-2 or PBP-3 or may be a particular enzyme involved in peptidoglycan synthesis.